Answer: y = -(x - 2)^2 - 4
Explanation:
If we have a function of the form:
y(x) = a*(x - b)^2 + c
The vertex of the function will be located at the point (b, c)
This happens because the square therm has a minimum (or maximum if a is negative) when x = b, so this is is the minimal value of x, and the minimal value of y is c.
Here in the graph, we can see that the vertex is at (-2, - 4) so we have that c = -4, and b = -2
the function is:
y(x) = a*(x + 2) - 4
And because the "hands" of the graph are coming down, we know that the value of a is negative, and the only option where a is negative, b = -2 and c = -4 is the third option:
y = -(x - 2)^2 - 4